The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2015gb005316
|View full text |Cite
|
Sign up to set email alerts
|

Forest harvest contribution to Boreal freshwater methyl mercury load

Abstract: Effects of Boreal forest harvest on mercury (Hg) and methyl mercury (MeHg) soil pools and export by stream runoff were quantified by comparing 10 reference watersheds (REFs) covered by >80 year old Norway spruce (Picea abies Karst.) forests with 10 similar watersheds subjected to clear-cutting (CCs). While total Hg soil storage did not change, MeHg pools increased seven times (p = 0.006) in the organic topsoil 2 years after clear-cutting. In undulating terrain, situated above the postglacial marine limit (ML) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 88 publications
6
45
0
Order By: Relevance
“…through forest harvest (clear-cut), after which increased Hg concentrations in water, zooplankton, and fish have been observed [9,16,17,18,19,20]. In two accompanying studies we reported that forest harvest lead to an enhanced MeHg formation in soils and an increased MeHg transport from the same study sites [21,22].…”
Section: Introductionmentioning
confidence: 71%
“…through forest harvest (clear-cut), after which increased Hg concentrations in water, zooplankton, and fish have been observed [9,16,17,18,19,20]. In two accompanying studies we reported that forest harvest lead to an enhanced MeHg formation in soils and an increased MeHg transport from the same study sites [21,22].…”
Section: Introductionmentioning
confidence: 71%
“…Not surprisingly, Hg mass positively correlated with depth of sampled mineral horizons (P = 0.01), explaining 45% of the variance in Hg mass across these soil pits. Compared to Hg mass in these Arctic tundra soils, mass estimates in temperate forest areas generally show smaller pool sizes, in the range of 120 to 170 g/ha in eastern Germany (Schwesig et al, 1999), 213 g/ha in the northeastern United States (Yu et al, 2014), 53 g/ha in mineral soils of a Minnesota forest (Grigal et al, 2000), and 12 to 80 g/ha in Swedish boreal forests (Kronberg, Drott, et al, 2016). Although comparisons across sites are challenging because different studies reference results to different soil depths, remote Arctic tundra soils show some of the highest Hg pools in soils compared to most temperate soils.…”
Section: Active-layer Hg Pool Sizes In Northern Alaska Arctic Tundra mentioning
confidence: 93%
“…This suggests that non-essential Hg in these aquatic consumers is associated with the retention of equally non-essential terrestrial OM, from a nutritional point of view (Grey et al, 2001;Jansson et al, 2007;Cole et al, 2011;Karlsson et al, 2012;Lau et al, 2012). The OM-Hg interactions have been intensively studied with a general consensus that OM mobilizes total Hg and MeHg from soil to waters (Skyllberg et al, 2000;Shanley & Bishop, 2012;Kronberg et al, 2016). The high abundance of cladocerans across oligotrophic lakes is strongly exposed to terrestrial food sources (Berggren et al, 2014) and, once ingested, Hg may be equally transferred via such terrestrial as well as algal food sources, as seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing DOC concentrations derived from terrestrial sources can themselves potentially increase Hg bioaccumulation in estuarine ecosystem food webs (French et al, 2014;Jonsson et al, 2014;Jonsson et al, 2017). This is also relevant in boreal ecosystems as common forest harvest activities can enhance terrestrial OM input to lake (Meunier et al, 2016), resulting in increased DOC concentrations (O'Driscoll et al, 2006;Glaz et al, 2015), and sometimes higher Hg and/or MeHg input from terrestrial to aquatic ecosystems (Eklöf et al, 2013;Kronberg et al, 2016). This can increase Hg bioaccumulation in food webs (Bishop et al, 2009;Hongve et al, 2012;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%